Southward displacement of the North Atlantic subtropical gyre circulation system during North Atlantic cold spells - Reißig, Stefan; Nürnberg, Dirk; Bahr, André; Poggemann, David Willem; Hoffmann, Julia (Paleoceanography and paleoclimatology, 2019)
Rapid subsurface oceanographic change in the tropical west Atlantic reflects shifting subtropical gyre - Subsurface warming responds to deglacial AMOC perturbations (Heinrich Stadials 2 and 1, and th...
Gesehen am 23.10.2019